Invasive Disease Potential of Pneumococcal Serotypes in Children After PCV13 Implementation. (4th July 2020) - Cohen, Robert; Levy, Corinne; Ouldali, Naim; Goldrey, Marie; Béchet, Stéphane; Bonacorsi, Stéphane; Varon, Emmanuelle
Abstract: We aimed to assess the invasive disease potential of non-PCV13 serotypes after the implementation of this vaccine. Most non-PCV13 serotypes had low invasive disease potential. Among serotypes with the highest invasive disease potential (12F, 24F, 38, 8, 33F, 22F, and 10A), all but 24F and 38 were included in PCV20.